The relationship between sedentary behavior and non-suicidal self-injury behavior among adolescents in China - Guo, Yaru; Yin, Xiaojian; Xu, Jianyi; Chen, Fule; Zhang, Feng; Liu, Yuan; Sun, Pengwei; Hong, Jun; Hu, Yanyan (Frontiers in Psychiatry, 2024)
BackgroundThe objective of this study was to explore the relationship between sedentary behavior and non-suicidal self-injury (NSSI), and to provide a theoretical basis for preventing and reducing the occurrence of NSSI behavior and the development of intervention measures.MethodsBetween September and December 2021, a sedentary behavior and NSSI survey was administered to 10327 Chinese adolescents aged 12–17 who had been randomly selected using the stratified cluster random sampling method. The results were analyzed using the chi-square test and logistic regression analysis to explore the relationship between sedentary behavior and NSSI in this population.ResultsThe study found an overall NSSI detection rate among the participants of 25.1%, with occasional NSSI and frequent NSSI detection rates of 11.0% and 14.1%, respectively. The NSSI detection rate is higher in girls than in boys. After controlling for related influencing factors, the NSSI detection rates among adolescents with sedentary behavior duration ≥8 hours and screen time ≥2 hours were 1.393(β= 0.332, P <0.01) and 1.569(β= 0.451, P <0.01) times higher than those with sedentary behavior duration <8 hours and screen time <2 hours, respectively.ConclusionSedentary behavior, especially that related to screen time is closely related to the occurrence of NSSI in adolescents. To reduce the occurrence of NSSI, we should therefore pay attention to the harmful effects of sedentary behavior on the physical and mental health of teenagers, take corresponding measures to limit sedentary behavior and screen time, and guide teenagers to use electronic devices correctly.